PREDICTIVE VALUE OF THE GLOBAL LONGITUDINAL STRAIN IN HYPERTROPHIC CARDIOMYOPATHY PATIENTS - S. M. Komissarova; E. Yu. Zakharova; Т. V. Sevruk; I. B. Ustinova; O. V. Krasko (Российский кардиологический журнал)
Aim. To evaluate prognositc role of the decrease of global longitudinal strain as a predictor of adverse outcomes in a large cohort or hypertrophic cardiomyopathy patients (HCMP).Material and methods. Totally, 262 HCMP patients investigated (162 males, 100 females) at the age 16-79 y. o. (median 48 y. o.), who, together with routine echocardiographical parameters, underwent registration of 2D Strain and estimation of the value of global longitudinal deformity. Clinical endpoints included mortality related to chronic heart failure (CHF) and hospitalization for CHF progression.Results.  During the follow-up (median 2,5 (0,2...5,1) years) in 11 among 262 patients (4,2%) with HCMP, there were adverse outcomes registered: sudden cardiac death (SCD) in 3 patients, resuscitated SCD and implanted cardioverter (ICD) — 1 patient, ICD shocks due to sustained ventricular tachicardia — in 2 patients, fatal outcome due to progression of CHF to an end stage — 5 patients, hospitalization due to CHF progression to III FC — 16 patients. Multifactorial analysis showed that independent factors for fatal outcome and hospitalization were the following: decrease of global longitudinal strain <13% (HR 28,5; 95% CI 2,9-278, p=0,004), AF episodes (HR 3,3; 95% CI 1,2-8,9, р=0,02) and CHF of III-IV FC NYHA (HR 4,2; 95% CI 1,2-14,9, р=0,028).Conclusion. The value of global longitudinal strain is associated with the development of adverse events related to progression of CHF in HCMP and might be applied in identification of patients with high risk of adverse CHF progression.